Pathogenic variants in SQOR encoding sulfide:quinone oxidoreductase are a potentially treatable cause of Leigh disease. Issue 5 (15th April 2020) - Friederich, Marisa W.; Elias, Abdallah F.; Kuster, Alice; Laugwitz, Lucia; Larson, Austin A.; Landry, Aaron P.; Ellwood‐Digel, Logan; Mirsky, David M.; Dimmock, David; Haven, Jaclyn; Jiang, Hua; MacLean, Kenneth N.; et al.
Abstract: Hydrogen sulfide, a signaling molecule formed mainly from cysteine, is catabolized by sulfide:quinone oxidoreductase (gene SQOR ). Toxic hydrogen sulfide exposure inhibits complex IV. We describe children of two families with pathogenic variants in SQOR . Exome sequencing identified variants; SQOR enzyme activity was measured spectrophotometrically, protein levels evaluated by western blotting, and mitochondrial function was assayed. In family A, following a brief illness, a 4‐year‐old girl presented comatose with lactic acidosis and multiorgan failure. After stabilization, she remained comatose, hypotonic, had neurostorming episodes, elevated lactate, and Leigh‐like lesions on brain imaging. She died shortly after. Her 8‐year‐old sister presented with a rapidly fatal episode of coma with lactic acidosis, and lesions in the basal ganglia and left cortex. Muscle and liver tissue had isolated decreased complex IV activity, but normal complex IV protein levels and complex formation. Both patients were homozygous for c.637G > A, which we identified as a founder mutation in the Lehrerleut Hutterite with a carrier frequency of 1 in 13. The resulting p.Glu213Lys change disrupts hydrogen bonding with neighboring residues, resulting in severely reduced SQOR protein and enzyme activity, whereas sulfide generating enzyme levels were unchanged. In family B, a boy had episodes of encephalopathy and basal ganglia lesions. He was homozygous for c.446delT and had severely reduced fibroblast SQOR enzyme activity and protein levels. SQOR dysfunction can result in hydrogen sulfide accumulation, which, consistent with its known toxicity, inhibits complex IV resulting in energy failure. In conclusion, SQOR deficiency represents a new, potentially treatable, cause of Leigh disease.